2012
DOI: 10.4049/jimmunol.1102136
|View full text |Cite
|
Sign up to set email alerts
|

The Size of the Plasmacytoid Dendritic Cell Compartment Is a Multigenic Trait Dominated by a Locus on Mouse Chromosome 7

Abstract: Plasmacytoid dendritic cells (pDC) compose one of the many distinct dendritic cell subsets. The primary function of pDC is to potently produce type 1 IFNs upon stimulation, which is highly relevant in antiviral responses. Consequently, the ability to manipulate the size of the pDC compartment in vivo may increase the capacity to clear viral infections. In an attempt to identify genetic loci affecting the size of the pDC compartment, defined by both the proportion and absolute number of pDC, we undertook an unb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Such differences among skin DC subsets are reminiscent of mouse-strain-specific expression of the endocytic receptor Langerin by LN-resident CD8+ DCs and gut DCs (21,22), and by the variations of plasmacytoid DC numbers linked to genetic polymorphisms (23,24). Footpads and the tail have a particularly protective stratum corneum, which might explain why immunosurveillance does not necessarily require the highly immunocompetent Langerin+ dDCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such differences among skin DC subsets are reminiscent of mouse-strain-specific expression of the endocytic receptor Langerin by LN-resident CD8+ DCs and gut DCs (21,22), and by the variations of plasmacytoid DC numbers linked to genetic polymorphisms (23,24). Footpads and the tail have a particularly protective stratum corneum, which might explain why immunosurveillance does not necessarily require the highly immunocompetent Langerin+ dDCs.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports showing the generation of free radicals during melanogenesis which hydroxylate tyrosinase and other proteins, thereby increasing their antigenicity (22,23). Elassiuty et al, showed upregulation of heme oxygenase-1 in patients' melanocytes due to high oxidative stress (24). The build-up of ROS along with possible immune system defects allows for the inappropriate autoimmune response against melanocytes.…”
mentioning
confidence: 99%
“…pDCs are major producers of IFNα . It has been noted that different mouse strains vary in capacity of IFNα production . We and others had recently found that pDCs from NZB/W F1 mice produce more IFNα in vitro than those from C57BL/6 mice .…”
Section: Discussionmentioning
confidence: 92%
“…5 It has been noted that different mouse strains vary in capacity of IFNa production. 17,18 We and others had recently found that pDCs from NZB/W F1 mice produce more IFNa in vitro than those from C57BL/6 mice. 19,20 Here we revealed further that between the two parent strains, NZW pDCs are the potent producers of IFNa than NZB pDCs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation